A novel cancelable fingerprint scheme based on random security sampling mechanism and relocation bloom filter. Issue 125 (February 2023) - Sun, Yanan; Li, Hengjian; Li, Nianqiang
Abstract: The existing cancellable fingerprint template based on the bloom filter either suffers from a lack of template security or low recognition performance. To solve the above problems, the paper proposes a novel cancelable fingerprint protection scheme based on a random sampling mechanism and relocation bloom filter. The security matrix is generated by a random sampling mechanism to increase the security and recognition accuracy of the scheme. The structure of a random sampling mechanism is as follows. Firstly, we use the key management system to generate keys and a chaotic matrix with randomness. Secondly, the key is used as a random initial address to extract overlapping feature sub-blocks from fingerprint features. Then the feature sub-blocks are combined to generate a feature matrix. Therefore, the feature matrix has richer fingerprint information than the original fingerprint features. Finally, a security matrix is generated by the XOR fusion of features matrix and chaotic matrix. Furthermore, we designed a relocation bloom filter with a parallel structure, which provides a way to avoid the decrease in performance caused by hash conflicts. What is more, it increased the security of the scheme that the relocatable bloom uses an irreversible function mapping function to transform the security matrix into a cancelable fingerprint template. The experimental results demonstrate that this scheme has state-of-the-art accuracy performance on benchmark FVC2002 and FVC2004 fingerprint databases. The security analysis shows that the scheme meets the cancellable biometrics protection scheme criteria and has higher security.